2022
DOI: 10.3389/fmed.2021.783757
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of ANCA Determine Different Clinical Phenotypes and Outcome in ANCA-Associated Vasculitis (AAV)

Abstract: AimAccumulating evidence supports the use of antineutrophil cytoplasmic antibody (ANCA) type to classify different clinical entities. We aimed to evaluate whether the presence and type of ANCA determine different diseases, based on clinical phenotypes, renal involvement, and response to treatment.Patients and MethodsDifferences in terms of clinical manifestations, disease activity, laboratory parameters, and histology were recorded between patients with focal necrotizing glomerulonephritis (FNGN) due to myelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Researchers suggested that the use of ANCA specificity rather than the use of clinical syndromes, to categorize the AAVs, 28,29 because MPO-AAGN and PR3-AAGN showed differences in clinical phenotype and renal histology. 30 In our cohort, the proportion of patients with normal glomeruli >25% (68.85%) was similar to the results of Saito et al, 14 and the proportion of patients with IFTA ≤ 25% (60.66%) was similar to the results of An et al, 26 with a high positivity rate for MPO-ANCA. However, the results of Mejia-Vilet et al showed the proportion of patients with IFTA > 25% with the lowest MPO-ANCA positivity was similar to our results (39.34%).…”
Section: Discussionsupporting
confidence: 91%
“…Researchers suggested that the use of ANCA specificity rather than the use of clinical syndromes, to categorize the AAVs, 28,29 because MPO-AAGN and PR3-AAGN showed differences in clinical phenotype and renal histology. 30 In our cohort, the proportion of patients with normal glomeruli >25% (68.85%) was similar to the results of Saito et al, 14 and the proportion of patients with IFTA ≤ 25% (60.66%) was similar to the results of An et al, 26 with a high positivity rate for MPO-ANCA. However, the results of Mejia-Vilet et al showed the proportion of patients with IFTA > 25% with the lowest MPO-ANCA positivity was similar to our results (39.34%).…”
Section: Discussionsupporting
confidence: 91%
“…ANCA(−) vasculitis also shows a higher percentage of sclerotic lesions and interstitial fibrosis, similar to the damages found in MPO-ANCA vasculitis [ 56 ]. A recent study that evaluated the association between ANCA specificity and histopathology findings revealed that 64% of PR3-ANCA patients had the crescentic phenotype and only 3% the sclerotic one [ 57 ]. On the other hand, renal histology in MPO-ANCA and ANCA(−) patients was similar, with only 28% having the crescentic and 46% the sclerotic phenotype.…”
Section: Renal Involvement—histopathologymentioning
confidence: 99%